Key Drivers for Differentiated Airport Passenger Service Charges. (1st May 2014) - Zuidberg, Joost
Recently, differentiations in airport charges have been the subject of juridical complaints. This study identifies key drivers for differentiated passenger service charges. The results suggest airports tend to apply differentiations in favour of their most important users. This is illustrated by the fact that hub airports are more likely to differentiate between transfer and origin/destination (O/D) passengers, while regional and public service airports tend to apply reduced tariffs for domestic passengers. However, applying charging structures in accordance with the wishes of an airport's most important user(s) may be in accordance with a more market-oriented strategy, leading to profit maximisation.